Policing Subversion in Post-Napoleonic Europe: Austria and the Greek Revolution of 1821–1830. Issue 2 (May 2023) - Aliprantis, Christos
This contribution examines the position of the Habsburg Empire vis-à-vis the Greek Revolution of 1821–1830 with a special focus on policing. It suggests that with its undeniable transnational significance and perceived threat against the status quo after 1815, the Greek Revolution pushed the Austrian state to enforce a variety of police measures to contain this alleged threat. These measures ranged from passport and border control directed towards moving Philhellenes, to monitoring Greek refugees and exiles, and using unofficial agents and consuls abroad to gather information on the rebellious Greeks. The article uses the Austrian police policies towards the Greeks as a vehicle to understand more widely how nineteenth-century policing functioned. Based on policing, the paper thus adds to the intellectual and administrative history of modern statehood.